Contribution of Daylighting to Saving Electrical Energy in Cameroon: Case Study of a Classroom in a Public School - Merimé Souffo Tagueu; Lionelle Adelaїde Madjou Tanekou; Benoît Ndzana (Journal of Engineering)
The need for electrical energy in Cameroon is growing and supply is not keeping up with demand. The solutions proposed so far relate to the construction of new hydroelectric dams and solar power plants, but this requires a lot of time and enormous financial resources. In this work, we develop a method for reducing the energy bill by adjusting lighting level while remaining within regulatory margins. This method highlights the use of a dimmer which allows the lighting level of the luminaires to be adjusted from 0% to 100% of their value. Thus, by combining the contribution of natural outdoor lighting with that of artificial indoor lighting, we are able to significantly reduce the quantity of electrical energy consumed by a classroom during the day. In our case study, by dividing the classroom into 99 measurement points, we collect data on illuminance levels by simulation using DIALux software and by direct measurement using a luxmeter. Applying the optimization algorithm designed for this purpose brings the average illuminance level down to 300lx following the EN12464 standard. Finally, taking into account the cost of kWh practiced in Cameroon, this saving goes up to 57.85% depending on the daily lighting level. This solution could make it possible to partially resolve the energy deficit in the time necessary for the construction of new power plants.